Increased Working From Home in Vocational Counseling Psychologists During COVID-19: Associated Change in Productivity and Job Satisfaction - Zürcher, Andrea; Galliker, Sibylle; Jacobshagen, Nicola; Lüscher Mathieu, Peter; Eller, Andrea; Elfering, Achim (Frontiers in Psychology, 2021)
During the COVID-19 pandemic, vocational counselors in Switzerland more frequently worked from home (WFH) and less frequently worked on-site. The aim of this study was to assess how WFH corresponds with indicators of job performance and occupational well-being. More specifically, the current questionnaire study analyzed the increase in WFH, self-reported productivity, distractibility in WFH, current job satisfaction, work-life balance in WFH, and feelings of loneliness. Findings showed that the increase in WFH in vocational counseling psychologists during the COVID-19 pandemic was associated with an increase in productivity and job satisfaction and with lower distractibility in WFH compared to work on-site. However, more frequent WFH was not significantly associated with improved work-life balance during the COVID-19 pandemic. Vocational counselors who shared the office on-site with many colleagues experienced higher feelings of loneliness during WFH. Vocational counselors regarded the condition of WFH as productive and satisfying while work-life balance did not improve. The discussion sheds light on the potential WFH-related increase of boundary management demands.